Development and validation of a LC-MS/MS method for ivermectin quantification in dried blood spots: application to a pharmacokinetic study in Trichuris trichiura-infected adults. Issue 24 (7th June 2018) - Schulz, Jessica D.; Neodo, Anna; Coulibaly, Jean T.; Keiser, Jennifer
Abstract : Ivermectin was quantified in dried blood spot and plasma samples derived from Trichuris trichiura -infected adults with a validated LC-MS/MS method. Abstract : Ivermectin serves as a good addition to the small group of medications for soil-transmitted helminths, particularly against Trichuris trichiura infections. So far, ivermectin has been poorly characterized in clinical trials to treat T. trichiura ; especially information on its pharmacokinetic (PK) behavior in infected populations is missing. Existing approaches to quantify ivermectin in human matrices are time-consuming, limited to matrixes of high volume and mostly do not distinguish between ivermectin and its metabolites. Thus, a sensitive, selective and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed to quantify ivermectin extracted from dried blood spots (DBS, micro-blood samples), plasma and blood. Method validation was performed on accuracy, precision, sensitivity, selectivity, linearity and stability. While the quantification of ivermectin in plasma and DBS was successfully validated, blood samples failed validation due to insufficient stability and robustness. The method was applied to samples from a clinical study with 11 adult volunteers from rural Côte d'Ivoire infected with T. trichiura sampled at 11 time points. Good agreement of the time-concentration profiles and PK parameters of plasma and DBS samples were achieved with e.g., a maximal concentration of 51.6 and 40.1 ng mL −1, respectively and identical time to reach maximal concentration of 3.9 h. Comparison of the results by Bland–Altman analysis resulted in high consistency. The less invasive and more patient-friendly DBS micro-blood sampling technique will be useful in future clinical trials to evaluate ivermectin's PK profile in larger populations.